Effects of quercetin on tenderness, apoptotic and autophagy signalling in chickens during post-mortem ageing. (30th July 2022) - Wang, Tongting; Feng, Xianchao; Li, Linzi; Luo, Jun; Liu, Xuebo; Zheng, Jun; Fan, Xiaojing; Liu, Yaping; Xu, Xinglian; Zhou, Guanghong; Chen, Lin
Highlights: Quercetin decrease the shear force and increase the MFI. Destruction of the myofibril structure of chicken meat occurred under quercetin. Apoptosis is induced by the mitochondria pathway and ER pathway. The expression of Beclin-1 and the transformation of LC3I to LC3II are promoted. The PI3K/Akt/mTOR pathway is activated. Abstract: The effect of quercetin on chicken breast muscle tenderness and the associated mechanism were investigated. The results indicated that quercetin significantly decreased the shear force and increased the myofibril fragmentation index (MFI). Haematoxylin-eosin-stained images showed that the internal structure of myofibril bundles in the quercetin-treated group was obviously degraded. Transmission electron microscopy showed that the myofibril structure, especially the M-line and A-band, was seriously degraded after quercetin treatment. Furthermore, quercetin treatment increased caspase-3 activity and the Bax/Bcl-2 ratio. The intensity of BiP, XBP1 and p-IRE1/IRE1 ratio increased significantly, and caspase-12 was activated. In addition, quercetin induced the transition from LC3I to LC3II and increased the expression of ATG7 and Beclin-1. The PI3K/Akt/mTOR signalling pathway was involved in the induction of autophagy and apoptosis by quercetin. These results indicated quercetin can promote meat tenderization, and activate apoptosis and autophagy pathways during post-mortem ageing.